Rare Case of Solitary Brain Metastasis from Colorectal Cancer - Ririhena, Fiorentina C; Aninditha, Tiara; Sofyan, Henry Riyanto; Madjid, Irma Savitri (Acta Neurologica Indonesia, 2026)
Introduction: Solitary brain metastasis (BM) from colorectal cancer (CRC) is rare (0.6–3.2%) and presents management challenges, especially in eloquent brain regions where surgical resection carries high risk. Stereotactic radiotherapy (SRT) is often preferred when surgery is not feasible, particularly in patients with good functional status. Case Illustration: A 49-year-old male with a KPS of 90 presented with worsening right-sided pulsating headaches for five days, accompanied by left-sided facial nerve palsy. MRI revealed a solitary intra-axial metastasis in the right temporal lobe, an eloquent region, with microbleeds and surrounding edema, suggestive of BM from rectal adenocarcinoma. Given the lesion's eloquent location, where surgery posed high risks, SRT was selected as the primary treatment modality, alongside corticosteroids for edema control and psychiatric support for depression Discussion: Solitary CRC BM in eloquent regions is a clinical dilemma. While surgery is standard for accessible lesions, SRT offers effective tumor control while reducing neurological complications, making it preferable for patients with high KPS (≥90) as it preserves cognitive function and improves survival outcomes. A multidisciplinary and holistic treatment approach, addressing both oncological and psychological aspects, is essential. Conclusion: Managing solitary CRC BM in eloquent brain regions requires special strategies. SRT was favored to reduce the risk of neurological impairment while maintaining tumor control, especially when surgery was not viable. A multidisciplinary approach is crucial to optimizing care and improving quality of life. Keywords: solitary brain metastasis, colorectal cancer, stereotactic radiotherapy, eloquent brain region